(3Ojf Gddg GdZGdH Ydi cd efcQ eHJOY cGPHs - (3GdehUdj, ejQ YKeGf Hf YHO GdLdjd GdehUdjs
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj CfRd GdaQbGf Ydi YHOg djchf ddYGdejf fPjQG (B... (3CeG HYO aEfj deG QCjJ GdeYGUj bO cKQJ hTGYJ hGdHOY bO XgQJ hPGYJ hGdTQjYI bO gLQJ hVGYJs
(3BNQgG (B:s
(3BNQgG(B: (3hGdJLfH Yf Gdghi hGdGNJQGY hYOe GdQchf hGdejd Edi GdOfjG hCgd GdRjZ hGdChVGY (B. (3SHMGf QHc QH GdYRI YeG jUahfs
(3JHUQI GdeDda (B:s
(3hLO aj GdeNWhW Cfg(B: (3YKeGf Hf SdjeGf Hf YHO GdLdjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf, L (B1: 483s
(3EjVGM Gdecfhf, L (B1: 483s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds